New Surgical Techniques for Early Stage Cervical Cancer Under 2 cm : Is There Enough Evidence? - Dogan, Nasuh Utku; Dogan, Selen (Asian Pacific journal of cancer prevention : APJCP, 2025)
Cervical cancer is the fourth most common malignancy in women worldwide and the second leading cause of cancer related mortality globally, making it a significant public health problem. Half of the women diagnosed are at an early stage; these women are typically young, mainly nulliparous, and have a long life expectancy. Less radical surgery is an attractive option for this selected group. In this narrative review, we aim to summarize the data regarding less radical surgery for early cervical cancer. Studies regarding less radical surgery including, conisation, simple trachelectomy and simple hysterectomy were searched in PUBMED database  in English and included from January 1995 to September 2024.Retrospective studies with a significant number of patients and  randomised controlled studies in this subject were included and discussed in detail as well. Retrospective studies have identified a low rate of parametrial involvement in specific subsets of patients with early cervical cancer, such as those with small tumor sizes (less than 2 cm), cervical stromal invasion less than 10 mm, no lymph node involvement, and no distant disease on imaging. In these patients, the incidence of parametrial involvement is less than 1%, which may render radical surgery unjustifiable. For this selected group, less radical surgery options, such as conization or simple hysterectomy, become attractive alternatives. When fertility preservation is desired, conization is an option; when fertility is not a concern, simple hysterectomy is the standard approach. Strict patient selection and preoperative evaluation are critical.